COMIC CODE: LINGUOSTYLISTIC MEANS OF REPRESENTATION (BY THE EXAMPLE OF THE ANALYSIS OF SHORT STORIES BY A. DAUDET AND O. MIRBEAU) - M. Voronkova; T. Samarskaya (Гуманитарные и юридические исследования)
The article deals with the problem of deciphering the code of a literary text, as one of the most pressing problems of modern linguistics. The article explores the work of the French writer Octave Mirbeau "Letters from my hut" in terms of the presence in it of the code of Alfons Daudet, the author of the cycle of stories "Letters from my mill". Octave Mirbeau is an active and influential participant in the historical events of France of the late 18th - early 19th century. His pen was ruthless, however, the dark sides of reality, through the comic code, he described so that they often became attractive. The article analyzes the implementation of the Alphonse Daudet code in Octave Mirbeau text space, allowing to prove the intertextual connection between their works. Attention is drawn to that Octave Mirbeau uses a comic code, as a technique for creating a common communicative ield, between the collection of stories "Letters from my hut" and the work of Alphonse Daudet "Letters from my mill". The paper proves that the intertextual connection between the designated works is carried out by a comic code, as a way of reproducing a precedent text, by creating caricature images. It is noted that the code sets a certain connotation to the text and its individual parts, imposes a value that can not be decrypted by the recipient who does not own a certain cultural code. The article touches upon the specifics of the Octawa Mirbeau ideology, which was influenced by various literary schools, works of other writers, important historical and social events, which explains the diversity of forms, genres and stylistic techniques used by them. The comic code is considered through the disagreement that existed between Alphonse Daudet and Octave Mirbeau in life, which is undoubtedly relected in the works. It is proved that Octave Mirbo coded his stories primarily at the comic level, creating literary caricatures similar to the cartoons of Alphonse Daudet. All translations are made by the authors of the article.